The use of artificial intelligence in the public sector in Shanghai: ambition, capacity and reality - Todaro, Diego (Palgrave Macmillan, 2024)
This book examines how Shanghai aims to improve public service provision by accelerating the use of artificial intelligence (AI) in the public sector. After clarifying the technical and social factors that shape the use of AI in this area, the book delves into the AI policy environment and AI ecosystem of Shanghai to gauge the city's capacity to implement public sector AI applications. Then it examines how this capacity translates into real-world policy initiatives through the investigation of case studies. It highlights the analytical, operational and political capabilities that determine the strengths and limitations of such initiatives in deploying AI in the public sector, and it assesses their impacts on public service provision in Shanghai. By using the findings on Shanghai to gain a deeper understanding of key topics in public sector AI research, this book also contributes new knowledge about the use of AI to improve the provision of public services
Glossar, Literaturverzeichnis: Seite 621-643, Index
Keywords: China; Shanghai regierungsunmittelbare Stadt; Hochschulschrift; Öffentlicher Dienst; Innovationsprozess; Künstliche Intelligenz; Schanghai